2016
DOI: 10.1063/1.4946023
|View full text |Cite
|
Sign up to set email alerts
|

Direct drive: Simulations and results from the National Ignition Facility

Abstract: Direct-drive implosion physics is being investigated at the National Ignition Facility. The primary goal of the experiments is twofold: to validate modeling related to implosion velocity and to estimate the magnitude of hot-electron preheat. Implosion experiments indicate that the energetics is well-modeled when cross-beam energy transfer (CBET) is included in the simulation and an overall multiplier to the CBET gain factor is employed; time-resolved scattered light and scattered-light spectra display the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In the cross-beam energy transfer (CBET) process [16], nonabsorbed light that is reflected or scattered from its critical surface or refracted from the underdense plasma acts as an electromagnetic seed for the stimulated Brillouin scatter of incoming (incident) light [17]. CBET has been shown to reduce the target absorption and resulting P abl of direct-drive ICF targets by as much as 40% on OMEGA [16] and 60% on NIF-scale targets [18]; hydrodynamic instabilities and lowmode drive asymmetries can reduce P hs and neutron rate, and the suprathermal electron generation by the twoplasmon-decay instability and stimulated Raman scattering [19] can preheat the DT fuel and raise α.…”
Section: =3mentioning
confidence: 99%
“…In the cross-beam energy transfer (CBET) process [16], nonabsorbed light that is reflected or scattered from its critical surface or refracted from the underdense plasma acts as an electromagnetic seed for the stimulated Brillouin scatter of incoming (incident) light [17]. CBET has been shown to reduce the target absorption and resulting P abl of direct-drive ICF targets by as much as 40% on OMEGA [16] and 60% on NIF-scale targets [18]; hydrodynamic instabilities and lowmode drive asymmetries can reduce P hs and neutron rate, and the suprathermal electron generation by the twoplasmon-decay instability and stimulated Raman scattering [19] can preheat the DT fuel and raise α.…”
Section: =3mentioning
confidence: 99%
“…We use a laser ray trace method for depositing the energy in the capsule, which takes into account the 3D pointing geometry, but does not include the effects of cross-beam energy transfer or nonlocal electron thermal transport. Both of these effects are known to be important for modeling laser-matter interactions in direct drive implosions, [24,25,26] but we have nonetheless found that the salient features of our shots are modeled well using a more approximate treatment. Our models employ multigroup diffusion for the propagation of radiation, and we apply a flux limiter to the electron ther- mal conduction in the ablator during the laser pulse.…”
Section: Model Description and Resultsmentioning
confidence: 83%
“…26. This has been shown to work well in PDD experiments with thicker CH shells, 43,44 and has also been used to design pointings for earlier NIF PDD exploding pusher implosions, including N120328. 37 Time-resolved x-ray images obtained on reference shot N120328 showed a fairly substantial non-uniformity with the implosion being oblate (diameter ~940 m by 800 m) in-flight at t=1.14 ns, even though SAGE simulations indicated that the implosion should be symmetric.…”
Section: Fig 7 Dmentioning
confidence: 97%